2005
DOI: 10.1016/j.ejvs.2004.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Life-style Modification in Peripheral Arterial Disease

Abstract: There is a lack of randomised controlled data proving the benefit of life-style modification in improving mortality and reducing cardiovascular events in patients with PAD. Despite this there is sufficient evidence to recommend some life-style modification as part of the overall approach to risk reduction in these patients. There is compelling evidence to support smoking cessation, increased exercise and improved diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 127 publications
1
20
1
3
Order By: Relevance
“…Clinical trials were not able to confirm the protective effects of these nutrients when observed in epidemiological studies. 7,9,10,[39][40][41][42][43] Although the antioxidant capacity is known to be reduced in subjects with PAD, 44 the results of the present study did not support the hypothesis of beneficial effects of vitamins C and E intake in atherosclerotic diseases.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Clinical trials were not able to confirm the protective effects of these nutrients when observed in epidemiological studies. 7,9,10,[39][40][41][42][43] Although the antioxidant capacity is known to be reduced in subjects with PAD, 44 the results of the present study did not support the hypothesis of beneficial effects of vitamins C and E intake in atherosclerotic diseases.…”
Section: Discussioncontrasting
confidence: 54%
“…Our finding of a negative association of PAD and fiber consumption, particularly fibers from fruits and whole grains, could suggest a protective role against PAD, independently of other dietary and non-dietary cardiovascular risk factors. In fact, such inverse association has already been described by some investigators, 44 but not in the Heart Professionals Follow-up Study. 8 Further studies are desirable to clarify these controversies.…”
Section: Discussionmentioning
confidence: 72%
“…Compared with age-matched controls, people with IC have a three to six fold increase in cardiovascular mortality (4). The majority of patients with IC are treated with best medical management (5).…”
Section: Discussionmentioning
confidence: 99%
“…Antiplatelet treatment is given to reduce the risk of cerebrovascular and coronary events. It is effective in the long-term secondary prevention of vascular events in people at high risk of vascular disease, including those who have had ischemic stroke or acute myocardial infarction (MI) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle modifications are currently the most cost-effective interventions 62 and there is compelling evidence to support smoking cessation, dietary changes and exercise. 63 Prevention of PAD With Diet and Lifestyle:…”
Section: Disclosuresmentioning
confidence: 99%